Video Layanan Masyarakat Desa Balunganyar Kecamatan Lekok Kabupaten Pasuruan - Achmad Nur Rofiuddin; Prafita Fardhany Aslam; Aji Arianto; Muhammad Catur Rizky; Sudjai Sudjai; Arif Rachman Putra; Didit Darmawan; Rommy Hardyansah; Rio Saputra; Mohammad Djaelani (BADAN PENERBIT STIEPARI PRESS, 2025)
In Balunganyar Village, Lekok, Pasuruan, access to information about public services is still limited. Most people in this village do not fully understand the types of services provided by the village government, the procedures for accessing these services, and the benefits that can be obtained. Based on the background that has been explained, there are several problems that need to be resolved through this program, namely how to increase awareness and understanding of the Balunganyar Village community about public services available in the village, then how to utilize video media as an effective communication tool in conveying public service information. The implementation of this PkM program uses a participatory approach, where the Balunganyar Village community is actively involved in the entire activity process, from planning, training, to evaluation. This approach was taken because active community participation is considered the key to success in improving their understanding and independence.